A THEORETICAL STUDY OF ELECTROMAGNETIC TRANSIENTS IN A LARGE CONDUCTING PLATE DUE TO CURRENT IMPACT EXCITATION - Mukerji, Saurabh Kumar; Singh, Ghanshyam Kumar; Goel, Sandeep Kumar; Manuja, Seema (E M W PUBLISHING, 2007)
Maxwell's equations are solved to determine transient electromagnetic fields inside as well as outside a large conducting plate of an arbitrary thickness. The plate is carrying a uniformly distributed excitation winding on its surfaces. Transient fields are produced due to sudden interruption of the d. c. current in the excitation winding. On the basis of a linear treatment of this initial value problem it is concluded that the transient fields may decay at a faster rate for plates with smaller value of relaxation time. It is also shown that the energy dissipated in the eddy current loss may exceed the energy stored in the initial magnetic field.